Pediatric Providers Are Not Following Guidance on Peanut Allergy in Infants. Issue 3 (May 2022) - Beal, Judy A.
Abstract : Guidelines on minimizing risks of infants developing peanut allergies were published in 2017 by the National Institute of Allergy and Infectious Diseases. Recent evidence suggests these guidelines are not being followed. Our pediatric nursing expert, Dr. Beal, summarizes the guidelines, offers resources to direct parents and caregivers who request more information, and highlights the important role of pediatric nurses in educating parents and caregivers.